The Effect of Auditor Quality on Financing Decisions - Chang, Xin; Dasgupta, Sudipto; Hilary, Gilles (The Accounting Review, 2009)
ABSTRACT: We present a model and provide empirical evidence showing that auditor quality affects the financing decisions of companies, and that higher audit quality reduces the impact of market conditions on client financial decisions and capital structure. Consistent with our analytical predictions, we find that companies audited by Big 6 firms are more likely to issue equity as opposed to debt than are those audited by small audit firms. We also find that companies audited by Big 6 auditors are able to make larger equity issues than are those audited by small auditors, but the difference narrows when market conditions improve. Additional results show that the debt ratios of companies decrease less in response to favorable market conditions when auditor quality is high, at least over the medium term.